Fundamentals and applications of metal nanoparticle- enhanced singlet oxygen generation for improved cancer photodynamic therapy - George, Blassan P.; Chota, Alexander; Sarbadhikary, Paromita; Abrahamse, Heidi (Frontiers in Chemistry, 2022)
The introduction of nanotechnology in the field of Photodynamic Therapy (PDT) has proven to have great potential to overcome some of the challenges associated with traditional organic photosensitizers (PS) with respect to their solubility, drug delivery, distribution and site-specific targeting. Other focused areas in PDT involve high singlet oxygen production capability and excitability of PS by deep tissue penetrating light wavelengths. Owing to their very promising optical and surface plasmon resonance properties, combination of traditional PSs with plasmonic metallic nanoparticles like gold and silver nanoparticles results in remarkably high singlet oxygen production and extended excitation property from visible and near-infrared lights. This review summarizes the importance, fundamentals and applications of on plasmonic metallic nanoparticles in PDT. Lastly, we highlight the future prospects of these plasmonic nanoengineering strategies with or without PS combination, to have a significant impact in improving the therapeutic efficacy of cancer PDT.